Volume 1: Offshore Technology 2009
DOI: 10.1115/omae2009-79413
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of Advanced Wave Analysis in Shallow Water Model Testing (Wave Splitting)

Abstract: The HAWAI JIP originated from the observed differences between model tests and numerical simulations in shallow water. These differences were identified as being caused by spurious free waves and reflected waves in the model basin. Identifying these waves and incorporating them in the numerical simulations greatly improved the agreement between the model test results and the simulation results. Although the effect of spurious waves is also present in deep water, the effect is most profound in shallow water. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The sloping bottom is 300-meter long and its slope is 1/20. According to recent researches, simulating wave propagation over sloping bottom requires special treatments because nonlinear low frequency component could be generated by reflection and shoaling (Voogt, 2005;Waals, 2009). Fig.…”
Section: Wish-offshorementioning
confidence: 99%
“…The sloping bottom is 300-meter long and its slope is 1/20. According to recent researches, simulating wave propagation over sloping bottom requires special treatments because nonlinear low frequency component could be generated by reflection and shoaling (Voogt, 2005;Waals, 2009). Fig.…”
Section: Wish-offshorementioning
confidence: 99%
“…By exploiting their different wavelengths and directions, we can reliably separate the three wave components at using a wave-splitting procedure [35,36]. We can assume , = ( ) to have the form: The magnitude of the difference-frequency wave amplitude, |A d |, is significantly lower than those at the wave frequencies, but it varies strongly with x.…”
Section: Wave-only Simulationmentioning
confidence: 99%
“…The results of past experiments [9] have shown that even a bathymetry as simple as a constant sloping seabed can be difficult to model accurately using a diffraction code. Extensive additional research is carried out in the HA W AI Joint Industry Project, [10] and [11], in which knowledge on waves from the field of coastal engineering is combined with the knowledge of hydrodynamics of moored vessels. The aim of that project is to gain insight in the complex physics related to the hydrodynamics of vessels moored in coastal areas.…”
Section: Time-domain Simulation Modelmentioning
confidence: 99%
“…Furthermore the interaction of waves in the basin with the headland or with the shallow water area near the location of the plant may be sources of low-frequency wave energy near the vessel, without these leading to vessel motions. Research such as performed in the HAWAI Joint Industry Project [10] and [11] is required to identify the wave-and shiprelated hydrodynamic processes involved.…”
Section: Need For Further Randdmentioning
confidence: 99%